Customer Satisfaction and Loyalty in E-Markets: A PLS Path Modeling Approach - Anderson, Rolph E.; Swaminathan, Srinivasan (Journal of marketing theory and practice, 2011)
This research investigates the factors that drive customer satisfaction and loyalty in e-markets. Employing qualitative interviews and field research, we identify key factors that drive customer satisfaction in e-businesses and use the partial least squares path modeling technique to evaluate their effect. Six factors are found to significantly affect satisfaction in e-businesses: adaptation, commitment, network, assortment, transaction ease, and engagement. Further, we discover that the positive effect of satisfaction on loyalty is moderated by customer trust and inertia. At lower levels of inertia and trust, customer satisfaction has a greater effect on loyalty. Actionable recommendations are provided for e-business managers to enhance customer satisfaction.